USING SOCRATIVE SERVICE IN ENGLISH LANGUAGE TEACHING FOR THE FORMATIVE ASSESSMENT IN THE NEW REALITY BY ZOOM - Aidarkhanova, A.A.; Degtyareva, X.S.; Yessenaman, S.Y. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2021)
Distance learning is becoming increasingly popular, whether for convenience, to accommodate work hours, or simply to have the ability to study from anywhere. And now, more than ever, with the coronavirus pandemic forcing people to stay at home, it's more critical. Modern realities force us to look for new ways of learning by using the latest information technologies. In the shortest possible time, we, teachers of a foreign language, had to choose from a huge number of offered educational platforms and services those that would help to continue the learning process in the best way, but already on the Internet space. An especially effective form of work with students is the work on the ZOOM educational platform. And nowadays it is not enough to use the only Zoom itself, it can be used within the internet source like Socrative with all the benefits.
Keywords: Zoom; Socrative; Distance learning; formative assessment